The Influence of Corporate Image, Price, and Word of Mouth on Repurchase Decisions with Customer Satisfaction as a Mediating Variable: A Study of Stone Crusher UPOYO Mandiri Sejahtera in Sleman - Kusumadevi, Dyaning Septiana; Sugandini, Dyah; Sutiono, Heru Tri (CV. Strata Persada Academia, 2025)
This study investigates the influence of corporate image, price, and word of mouth on repurchase decisions, with customer satisfaction as a mediating variable, in the context of the heavy equipment material industry. Using a quantitative correlational design, the research was conducted on 100 purposively selected buyers of Stone Crusher Upoyo Mandiri Sejahtera in Sleman, Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that corporate image and word of mouth significantly affect repurchase decisions, while price does not. Furthermore, although corporate image, price, and word of mouth positively influence customer satisfaction, satisfaction does not significantly impact repurchase behavior and fails to mediate any of the proposed relationships. These results underscore the unique dynamics of high-value B2B industrial purchasing behavior, where repurchase decisions are primarily driven by rational factors such as product life cycles, project requirements, and capital investment planning, rather than emotional constructs like satisfaction. Theoretically, this study contributes to the refinement of consumer behavior models by highlighting the limited mediating role of satisfaction in industrial contexts. Practically, it suggests that companies should focus on improving post-sale service responsiveness, pricing transparency, and strategic loyalty programs to enhance customer retention in cyclical and investment-intensive markets.